Serpentinization-associated travertines as spatio-temporal archives for lipid biomarkers key for the search for life on Mars - Sánchez-García, Laura; Carrizo, Daniel; Jiménez-Gavilán, Pablo; Ojeda, Lucía; Parro, Víctor; Vadillo-Pérez, Iñaki (Elsevier, 2024)
Serpentinization is a well-known aqueous alteration process that may have played important roles in the origins and early evolution of life on Earth, and perhaps Mars, but there are still aspects related to biomarker distri- bution, partitioning, and preservation that merit further study. To assess the role that precipitation of carbonate phases in serpentinization settings may have on biomarker preservation, we search for life signs in one of the world’s largest outcrops of subcontinental peridotites (Ronda, South Spain). We investigate the organic record of groundwater and associated carbonate deposits (travertines) in seven hyperalkaline springs, and reconstruct the biological activity and metabolic interactions of the serpentinization-hosted ecosystem. We identified lipid biomarkers and isotopic evidences of life, whose concentration and variety were much lower in groundwater than travertine deposits (ppb/ppt versus ppm level). Groundwater carried organics of abiotic (n-alkanes with values of CPI ~ 1) and/or biotic origin, of fresher (e.g. acids or alcohols) or more diagenetized (mature hopanes and n-alkanes) nature. In contrast, associated travertines held a more prolific record of biomarkers incorporating (molecular and isotopic) fingerprints of surface (mostly phototrophs) and subsurface (chemolithotrophs, methanogens and/or methanotrophs) life. Serpentinization-associated travertines seem to act as biomolecule archives over time fed by autochthonous and allochthonous sources, hence amplifying the dim biological signal of groundwater. These results illustrate the relevance of serpentinization-associated surface mineral deposits in searching for traces of life on analogous environments on Mars. We highlight the diversity of lipids produced in serpentinizing land environments and emphasize the potential of these geostable biomolecules to preserve fin- gerprints of life.
Keywords: Marcadores bioquímicos; Lipid biomarkers; Preservation; Biogenicity; Serpentinization; Mars